Role of the membrane potential in bacterial resistance to aminoglycoside antibiotics. - Damper, P D (1981)
The electrical potential difference (delta psi) across the membrane of Escherichia coli was measured by the distribution of lipid-soluble cations and correlated with resistance to dihydrostreptomycin, where resistance is presumed due to reduced uptake of the drug. A good correlation between the two measured parameters was found under all conditions tested, which included effects of several mutations, inhibitors, changes in pH, and osmolarity. The most dramatic changes were seen when pH was varied; in wild-type strains resistance increased more than 100-fold, and delta psi fell by 70 mV when pH was reduced from 8.5 to 5.5. These results were interpreted as support for a model in which the uptake of the polycationic aminoglycosides is electrogenic and therefore driven by delta psi. The factor common to mutations and conditions which increase resistance was a reduction in delta psi. A simple model was developed which relates the minimal inhibitory concentration to the rate of aminoglycoside uptake and the rate of growth.